The Efficacy and Safety of Janus Kinase Inhibitors for Patients With COVID-19: A Living Systematic Review and Meta-Analysis - Zhang, Xueyang; Shang, Lianhan; Fan, Guohui; Gu, Xiaoying; Xu, Jiuyang; Wang, Yeming; Huang, Lixue; Cao, Bin (Frontiers in Medicine, 2022)
Abstract Background: Cytokine storm observed in severe Coronavirus Disease 2019 (COVID-19) patients contributes to poor clinical outcomes and increased mortality. We aim to conduct a living systematic review and meta-analysis of the literature investigating efficacy and safety of Janus kinase (JAK) inhibitors for COVID-19 patients. Methods: Databases were searched up to December 1st, 2021 for interventional and observational studies comparing JAK inhibitor treatment with concurrent control in COVID-19 patients. Efficacy and safety outcomes were evaluated by pooled risk ratio (RR). Results: Of 3170 records retrieved, 15 studies were eligible, and 13 were evaluated in meta-analysis (n=3977). Based on data from three RCTs, baricitinib treatment significantly decreased mortality by day 28 in hospitalized COVID-19 patients (RR=0.64, 95% CI 0.51-0.80) without increasing the incidence of adverse outcomes. In subgroup analysis, patients requiring supplemental oxygen (RR=0.62, 95% CI 0.41-0.95) or high-flow oxygen/non-invasive ventilation (RR=0.59, 95% CI 0.42-0.85) at baseline benefited most. Pooled analysis of all eligible studies for JAK inhibitors (baricitinib, ruxolitinib, tofacitinib, and nezulcitinib) demonstrated a significant decrease in mortality (RR=0.62, 95% CI 0.49-0.78) with no increase in risk of adverse events. Conclusion: Baricitinib probably decreases mortality in hospitalized adult COVID-19 patients, especially for patients requiring supplemental oxygen or high-flow oxygen/non-invasive ventilation at baseline. The efficacy and safety of other JAK inhibitors such as ruxolitinib, tofacitinib, and nezulcitinib await more evidence. Study Registration: The study was registered in PROSPERO (CRD42021261414).